Pengaruh beban lampu terhadap tegangan, arus, dan RPM pada turbin angin ODGV 7 sudu - Rulyk Suhartono; Basuki Basuki; Mochamad Arif Irfa`i (Universitas Muhammadiyah Metro, 2022)
Renewable energy is energy that can replace fossil energy that will run out, renewable energy sources can come from the sun, water, geothermal, biomass and wind. Based on this explanation, the researchers conducted research on the conversion of wind energy into electricity by making ODGV wind turbines, for the purpose of this study was to find out how the number of blades and the load affect the performance of ODGV type wind turbines. The type of research that the author uses is quantitative research, in this method the author conducts research using a total of 7 blades and variations in lamp load 0, 3, 6 and 9 watts. The analyzed values ​​include voltage, current and revolutions per minute. From the results of the study, it was found that the ODGV wind turbine with a total of 7 blades produced a maximum value, namely, a voltage of 10 volts, a current of 0 watts and an RPM of 280.4 with a lamp load of 0 watts.